(untitled) (Bulletin of Innovative Research, 2026)
The technology of storing beetroot in temporary storage is covered. The study analyzed the morpho-biological properties of beetroot, its requirements for respiration intensity, humidity and temperature, and physiological and biochemical changes occurring during storage. The optimal storage regimes in temporary storages (above-ground and semi-underground piles, trenches) are justified - the temperature should be 0…+2 °C, relative humidity 85–95%. It serves to develop scientifically based recommendations to maintain quality indicators (dry matter, sugar content, appearance) and minimize losses during storage in temporary storages.